(untitled) (Medical Forum Monthly, 2024)
Objective: To determine Plasmodium species, clinical features, and hematological changes in Malaria. Study Design: Prospective Descriptive Study. Place and Duration of Study: This study was carried out at the Paediatric Departments of Shaheed Mohtrama Benazir Bhutto Medical University at Ghulam Muhammad Mahar Medical college Hospital Sukkur and Chandka Medical Collage Larkana, from July 2007 to July 2011. Patients and Methods:, This is prospective descriptive study, including 250 patients with fever and malaria confirmed on microscopy and immunochromatography, at both departments were included. After consent a separate pro- forma was filled for each patient to record demography and data about clinical presentation and laboratory investigations. Results: Out of 250 malaria cases, the classical clinical presentation was found in 198 (79.2%) of patients while 52 (20.8%) had other symptoms. Males were in majority 164 (65.6%) and age range 1 year to 12 years. Splenomegaly was found in 135 (54%) and hepatomegaly in 86 (34.4%) of patients. Microscopy results of malaria patients revealed P. Falciparum in 97 (38.8%), P. Vivax 91 (36.4%) and 62 (24.8%) mixed infection of P. Falciparum and P. Vivax. Anemia was found in most of patients 84% (Hb < 10g/dl). Thrombocytopenia (platelets < 150,000/cmm) was found in 50 (20%) of patients. Conclusion: The classical presentation of Malaria was seen in majority of cases but one should be careful about atypical or very serious complicated clinical presentation of malaria, and early diagnosis of P. falciparum or mixed infection is very essential to save the life of young children.